HIV-1 RT-Associated RNase H review - Madonna M. A. Mitry; Nermin S. Abdou; Rabah A. T. Serya (Ain Shams University, 2018)
HIV-RT is an essential enzyme for HIV replication it comprises two associated functions: RNA- and DNA-dependent DNA polymerase (RDDP & DDDP) and ribonuclease H (RNase H). The RNase H is function to cleave RNA strand in RNA/DNA hybrid intermediate in the reverse transcription process. Currently, successful inhibitors target the polymerase function of HIV-RT. RNase H evolves to be a promising target for anti-HIV drug research. This review describes the compounds reported as HIV-1 RNase H inhibitors.